RNA sequencing provides insights into the effect of dietary ingestion of microplastics and cadmium in the sea cucumber Apostichopus japonicus - Zhang, Chenxi; Zhang, Libin; Li, Lingling; Mohsen, Mohamed; Su, Fang; Wang, Xu; Lin, Chenggang (Frontiers in Marine Science, 2023)
Microplastics (MPs) and cadmium (Cd) are persistent pollutants in aquatic environments. Sea cucumbers are susceptible to MPs and Cd due to their feeding behavior. This study, based on Illumina sequencing, compared the transcriptomes of A. japonicus before and after Cd and/or MPs exposure. Additionally, we detected the changes of catalase (CAT), and superoxide dismutase (SOD) activity, glutathione (GSH), and malondialdehyde (MDA) content in the coelomic fluid of sea cucumbers. High concentration of MPs caused the increase of SOD activity. High concentration combined treatment resulted in significant up regulation of these four indicators in A. japonicus and had the largest number of differential expression genes (DEGs) reaching 1,618 DEGs, consisting of 789 up regulated along with 829 down regulated DEGs. Transcriptome results showed that Cd induced up regulation of intestinal FAS associated death domain protein (FADD) expression, which may cause apoptosis and inflammation. The increase of intestinal putative heparan sulfate 2-O-sulfotransferase in cadmium treatment groups provided a mechanism for host defense. The imbalance of expression of the NOD-like receptor (NLR) family inflammatory bodies and caspase 6 in the microplastic treatment group also led to the inflammatory reaction in the intestine of sea cucumber. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis showed that in the process of fatty acid metabolism, MPs and Cd showed antagonistic effects, mainly in the inconsistent expression of Stearoyl CoA Ddesaturase (SCD1) protein. The significant changes of Toll interacting protein (TOLLIP) and E-selectin (SELE) in all Cd and MPs treatment groups may indicate the key immune response genes of sea cucumber to Cd exposure and MPs exposure. These genes were involved in the immune defense of sea cucumber exposed to different levels of Cd and MPs. This study provided insights into the mechanism of dietary MPs and Cd intake in an economically and ecologically important invertebrate species.